Features of becoming and development of cultural and leisure practices in Ancient Greece - I. V. Petrova (Ukrainian Cultural Studies, 2017)
The analysis features of becoming and development of cultural and leisure practices in Ancient Greece is the goal of the article. The author justifies the preconditions which formed the appropriate hierarchy of life values of ancient Greek and reated the base for leisure development in Ancient Greece. It has been determined the leading preconditions such as absolute kosmolohizm, religiosity and polytheism, mental features of ancient Greeks and agon of Greek life, human cultural activity, polis political system, special perception of freedom as condition of absence of bright expressed domination over the human and strict regulation of the individual behavior, his personality initiative, existence of free time that isn’t occupied by routine and care of urgent daily needs. It has been revealed the essence of such cultural and leisure practices as symposiya, gymnasiya, professional, religious and political groups, agons, theatrical performances, visiting of agora and organization of events. It has been argued that the general patriarchal orientation of Greek civilization affected the system of leisure organization in Ancient Greece. It has been justified the opinion that value of leisure was being determined by its role in the aid of social balance: between the tendencies to integration and differentiation of society and to its unification and hierarchy. Therefore, there were coexistent leisure forms connected with the opposite social tendencies: some leisure demonstrations were acceptable for all (or for most) groups of population, they united and consolidated it, and others, limited by some requirements, extended social, cultural and political differences. Consequently there is a distribution of leisure practices on private (in which people could to participate according to their interests), and social (collective); obligatory (the participation was compulsory), and voluntary (choice of which depended only on desires of people); "high" (addressed only to mental and physical development of people), and "inactive" (passive recreation, entertainment or bodily pleasure).